CRITERION (PREDICTIVE) VALIDATION STUDY OF RELIGIOUS SCHEME SCALE - Budiarto, Yohanes (Jurnal Psikologi : Media Ilmiah Psikologi, 2017)
Abstract The purpose of this study was to confirm the factors of Religious Scheme Scale (RSS) using Indonesian Christian student sample. Participants were 230 students (male n= 100, female = 130) with age ranged from 15 – 23 years old (M = 16.8, SD = 1.588). Factor Analysis using Confirmatory Factor Analysis (CFA) was conducted using AMOS 21 did not confirm the 15 – item 3 – factor as proposed by Streib et al. (2010) but 13 – item 3 factor model. The unsatisfactory 2 variables were found in xenosophia sub scale. This study was considered similar to Proios’ study (2015) in Greece which dropped 2 items from xenosophia sub scale. The predictive validity of RSS showed a good predictor of identity fusion. In conclusion, RSS is satisfactory to be implemented in Indonesian Christian student samples. Keywords: Religious Scheme Scale, Factor analysis, Indonesian Christian students sample AbstractsTujuan dari penelitian ini adalah untuk mengkonfirmasi faktor Skala Skema Keagamaan (RSS) dengan menggunakan sampel siswa Kristen Indonesia. Peserta adalah 230 siswa (laki-laki n = 100, perempuan = 130) dengan usia berkisar antara 15 - 23 tahun (M = 16,8, SD = 1,588). Analisis Faktor menggunakan Analisis Faktor Konfirmasi (CFA) yang dilakukan dengan menggunakan AMOS 21 tidak mengkonfirmasi faktor 15 item 3 seperti yang diusulkan oleh Streib dkk. (2010) namun model faktor 13 - item 3. 2 variabel yang tidak memuaskan ditemukan pada sub skala xenosophia. Studi ini dianggap serupa dengan studi Proios (2015) di Yunani yang menjatuhkan 2 item dari sub skala xenosophia. Validitas prediktif RSS menunjukkan prediktor fusi identitas yang baik. Kesimpulannya, RSS cukup memuaskan untuk diimplementasikan dalam sampel siswa Kristen Indonesia. Kata kunci: Skala Skema Agama, Analisis Faktor, Sampel Mahasiswa Kristen Indonesia